2021
DOI: 10.1177/21501351211007808
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Ductal Stenting for Single Ventricle Patients Led to Improved Survival: An Institutional Case Series

Abstract: Background: The use of systemic-to-pulmonary shunts (SPS) in neonates with single ventricle heart defects and ductal-dependent pulmonary blood flow (ddPBF) was historically associated with high morbidity and mortality at our center. As a result, we transitioned to the preferential use of ductus arteriosus stents (DS) when feasible. This report describes our initial results with this strategy. Methods: A single-center study of single ventricle patients that received DS or SPS from 2015 to 2019 was performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…For example, among patients with single-ventricle anatomy, Meadows et al 27 mortality, transplant rates, and pulmonary artery growth between stent and shunt groups, although with higher planned reintervention rates in the stent group. Prabhu et al 28 found that PDA stenting was associated with reduced in-hospital morbidity and increased survival to stage II palliation in patients with single-ventricle physiology compared with surgical shunt. Therefore, it seems that for this group of patients, PDA stenting represents a comparable or even superior palliation strategy to surgical shunting.…”
Section: Discussionmentioning
confidence: 99%
“…For example, among patients with single-ventricle anatomy, Meadows et al 27 mortality, transplant rates, and pulmonary artery growth between stent and shunt groups, although with higher planned reintervention rates in the stent group. Prabhu et al 28 found that PDA stenting was associated with reduced in-hospital morbidity and increased survival to stage II palliation in patients with single-ventricle physiology compared with surgical shunt. Therefore, it seems that for this group of patients, PDA stenting represents a comparable or even superior palliation strategy to surgical shunting.…”
Section: Discussionmentioning
confidence: 99%
“…Interstage mortality and unplanned reintervention did not differ between the groups. In contrast, Prabhu et al[9], reporting outcomes in SV infants after DS (n = 11) and BTTS (n = 23), found a higher proportion of survival to stage II surgery after DS (100% versus 64%, p = 0.035). Our data contributes to the evidence that interstage mortality and unplanned re-interventions are similar after DS and BTTS in SV patients.…”
mentioning
confidence: 85%